Writing business bids & proposals for dummies - Cobb, Neil (Writer on business writing); Divine, Charlie (Chichester, West Sussex : John Wiley & Sons, 2016)
Congratulations! You have in your hands the collected knowledge and skills of the professional proposal writer -- without having to be one! Inside, you'll find out how to unlock what these professionals know and apply it to your own business to improve the way you capture new customers and communicate with existing ones! --Publisher
Understanding proposal development -- Focusing on your customer -- Planning your approach -- Creating your proposal -- Taking your proposal to the next level -- Parts of tens.
Includes index.
Keywords: Proposal writing in business; BUSINESS & ECONOMICS / Business Writing; Proposal writing in business